Business Model in The Individual Financial Statements of Banking Enterprises - Dariusz ADRIANOWSKI (Communications of International Proceedings, 2022)
This article outlines the general concepts of the business model and a business model of a banking enterprise. The study presents the basic definitions and components of business models. Particular attention was paid to the obligation to include information on business models in the banking enterprise reports. The purpose of this article is to verify how much space is devoted to business models in the bank individual financial statements. This article is both review and empirical. The theoretical part is based on the domestic and foreign literature. The research part was developed based on the analysis of the individual financial statements of the 10 largest banks in Poland.
Keywords: business model; individual financial statement; banking enterprise